Efficacy of Different Progestins in Women With Advanced Endometriosis Undergoing Controlled Ovarian Hyperstimulation for in vitro Fertilization-A Single-Center Non-inferiority Randomized Controlled Trial - Guo, Haiyan; Li, Jianghui; Shen, Xi; Cong, Yanyan; Wang, Yun; Wu, Ling; Li, Bin; Gao, Hongyuan; Ma, Meng; Zhang, Wei; Mao, Xiaoyan; Fu, Yonglun; et al. (Frontiers in Endocrinology, 2020)
Object: Is it possible to use different progestins cotreatment with human menopausal gonadotrophin (hMG) in women with advanced endometriosis but normal ovulation during controlled ovarian hyperstimulation (COH) in vitro fertilization (IVF)? Whether different progestins treatments can be an alternative choice for women with severe endometriosis in considering IVF/ICSI treatment remains unknown? Design: Non-inferiority randomized clinical trial. Setting: Tertiary-care academic medical center. Population: Four hundred and fifty infertile patients with severe endometriosis undergoing IVF/ICSI between May 2016 and March 2017. Methods: Four hundred and fifty infertile patients with severe endometriosis undergoing IVF/ICSI were randomized to: medroxyprogesterone acetate +hMG; dydrogesterone +hMG; and progesterone +hMG. Ovulation was induced with a gonadotropin-releasing hormone agonist (GnRH-a) and chorionic gonadotropin (hCG). Viable embryos were cryopreserved for later transfer. Main Outcome Measures: The primary endpoint outcome was the number of oocytes retrieved. Secondary indicators included the incidence of a premature surge in luteinizing hormone (LH), the number of viable embryos, and clinical pregnancy outcomes. Results: The number of oocytes retrieved was higher in the medroxyprogesterone acetate +hMG group than the two other groups (9.3 ± 5.7 vs. 8.0 ± 4.5 vs. 7.8 ± 5.2, P = 0.021). LH levels were suppressed after a 6-day progestin treatment in the medroxyprogesterone acetate +hMG and dydrogesterone +hMG groups, but there was a rebound of LH values in the progesterone +hMG group. No premature LH surge and ovarian hyperstimulation syndrome (OHSS) occurred. No significant differences among the three groups were observed in fertilization and pregnancy outcomes. Conclusion: It is mandatory to point out that our conclusions are valid for patients with ovarian advanced endometriosis but normal ovarian functions. These results suggest three different progestins protocols are equivalent in terms of pregnancy outcomes for women with advanced endometriosis. PPOS protocol can be an alternative choice for women with severe endometriosis and normal ovarian reserve in IVF/ICSI treatment. These methods could be tested with other populations of women with endometriosis. Clinical Trial Registration:www.ClinicalTrials.gov, identifier:ChiCTR-OIN-16008529. Trial registration date: 2014-05-25. Date of first patient enrollment: May 2016